Cognitive Skills and the Development of Strategic Sophistication - Eduardo Fe; David Gill (Institute of Labor Economics (IZA), 2018)
In this paper we investigate how observable cognitive skills influence the development of strategic sophistication. To answer this question, we study experimentally how psychometric measures of theory-of-mind and cognitive ability (or 'fluid intelligence') work together with age to determine the strategic ability and level-k behavior of children in a variety of incentivized strategic interactions. We find that better theory-of-mind and cognitive ability predict strategic sophistication in competitive games. Furthermore, age and cognitive ability act in tandem as complements, while age and theory-of-mind operate independently. Older children respond to information about the cognitive ability of their opponent, which provides support for the emergence of a sophisticated strategic theory-of-mind. Finally, theory-of-mind and age strongly predict whether children respond to intentions in a gift-exchange game, while cognitive ability has no influence, suggesting that different psychometric measures of cognitive skill correspond to different cognitive processes in strategic situations that involve the understanding of intentions.
Keywords: C91; D91; J24; 330; cognitive skills; theory-of-mind; cognitive ability; fluid intelligence; strategic sophistication; age; children; experiment; level-k; bounded rationality; non-equilibrium thinking; intentions; gift-exchange game; competitive game; strategic game; strategic interaction